Exploring the larval fish community of the central Red Sea with an integrated morphological and molecular approach. - Stamatina Isari; John K Pearman; Laura Casas; Craig T Michell; Joao Curdia; Michael L Berumen; Xabier Irigoien (PLoS ONE)
An important aspect of population dynamics for coral reef fishes is the input of new individuals from the pelagic larval pool. However, the high biodiversity and the difficulty of identifying larvae of closely related species represent obstacles to more fully understanding these populations. In this study, we combined morphology and genetic barcoding (Cytochrome Oxidase I gene) to characterize the seasonal patterns of the larval fish community at two sites in close proximity to coral reefs in the central-north Red Sea: one shallower inshore location (50 m depth) and a nearby site located in deeper and more offshore waters (~ 500 m depth). Fish larvae were collected using oblique tows of a 60 cm-bongo net (500 μm mesh size) every month for one year (2013). During the warmer period of the year (June-November), the larval fish stock was comparable between sampling sites. However, during the colder months, abundances were higher in the inshore than in the offshore waters. Taxonomic composition and temporal variation of community structure differed notably between sites, potentially reflecting habitat differences, reproductive patterns of adults, and/or advective processes in the area. Eleven out of a total of 62 recorded families comprised 69-94% of the fish larval community, depending on sampling site and month. Richness of taxa was notably higher in the inshore station compared to the offshore, particularly during the colder period of the year and especially for the gobiids and apogonids. Two mesopelagic taxa (Vinciguerria sp. and Benthosema spp.) comprised an important component of the larval community at the deeper site with only a small and sporadic occurrence in the shallower inshore waters. Our data provide an important baseline reference for the larval fish communities of the central Red Sea, representing the first such study from Saudi Arabian waters.